Reibenergieverteilungen von Mahlkugelkontakten. Issue 3 (7th February 2014) - Köster, Alexander; Scherge, Matthias; Teipel, Ulrich; Teipel, Ulrich; Weber, Alfred
<x xml:space="preserve">Abstract</x> The frictional contact between grinding bodies is determined by a characteristic course of the coefficient of friction. This periodic course can be transferred by a fundamental energy approach in the occurring energy of friction wherein the maximum is located in the rising half and the minimum in the dropping half of one contact zone. Crucial influencing variables are the ball diameter as well as intrinsic effects.